Morphological range changes in Mexican Astragalus radicans Hornem. (Fabaceae: Galegeae): review of its taxonomy and nomenclature - Estrada Castillón, Eduardo; Villarreal Quintanilla, José Ángel; Salinas, Alfonso-Delgado (Phytotaxa, 2020)
Continuing with the study of the Astragalus of Mexico and based on the measurement of 30 morphological characters and applying multivariate statistics, the two varieties of Astragalus radicans: A. radicans var. radicans and A. radicans var. harshbergeri were ranked at the species level and have their nomenclature updated. The results of the analysis allow the two infraspecific constitute isolated groups without overlapping between their individuals; therefore, they are raised from varieties to species, Astragalus radicans and Astragalus harshbergeri. A map with the updated distribution was included, and a dichotomous key is provided to identify the species. Both species are placed under the category of Threatened.